THE EFFECT OF GREEN ACCOUNTING AND FIRM SIZE ON FINANCIAL REPORT PERFORMANCE (EMPIRICAL STUDY OF MINING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2017-2021) - Salim, Maharani Juniar Mulyadi; Eksandy, Arry; Sofia, Irma Paramita (ZILLZELL MEDIA PRIMA, 2023)
This study aims to be able to explain the effects of green accounting, firm size and financial statement performance by taking empirical studies on mining sector companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021. The sample in this study is a mining sector company that is considered to have a lot of impact on the environment and has a high risk of environmental damage. This is due to natural resources being taken by companies continuously. The analysis in this study is an analysis carried out using the statistical application Econometric Views (EViews) version 12. Based on the calculation results, it is found that green accounting has no effect on financial statement performance. Meanwhile, it is known that firm size influences the performance of financial statements.